Features of sarcoidosis associated with chronic disease - Baughman, Robert P.; Lower, Elyse E (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2015)
Background: The clinical outcome of sarcoidosis is variable. Several features have been proposed as predictive of chronic sarcoidosis. Objectives: To examine the predictive role of clinical features on the clinical outcome score (COS) of sarcoidosis patients five years after initial diagnosis. Methods: A cohort of newly diagnosed sarcoidosis patients seen at one clinic were re-evaluated five years after initial diagnosis. The COS was determined at this five year time point and compared to initial age, race, sex, forced vital capacity (FVC) and chest roentgenogram. We also compared COS to whether patients had Lofgrens syndrome, lupus pernio, or cardiac disease and what treatment they received during the five years of observation. Patients with neurologic disease were divided into those with seventh cranial nerve paralysis alone versus those with other neurologic disease (CNS). Results: Of the 335 newly diagnosed patients seen over a three year period, 213 (64%) were evaluated five years after initial diagnosis. Of these patients 168 (79%) were still requiring systemic therapy at five years (COS 7, 8, or 9). Seven features were associated with chronic disease: CNS alone (Odds Ratio (OR)=19.24, p